Uptake of first two doses of human papillomavirus vaccine by adolescent schoolgirls in Manchester: prospective cohort study. Issue 7652 (24th April 2008) - Brabin, Loretta; Roberts, Stephen A; Stretch, Rebecca; Baxter, David; Chambers, Gloria; Kitchener, Henry; McCann, Rosemary
Abstract : Objective To assess the feasibility and acceptability of delivering a human papillomavirus (HPV) vaccine to adolescent girls. Design Prospective cohort study. Setting 36 secondary schools in two primary care trusts in Greater Manchester, United Kingdom. Participants 2817 schoolgirls in year 8 (12 and 13 year olds). Intervention Delivery of the bivalent vaccine at 0, 1, and 6 months over one school year. Main outcome measures Vaccine uptake for doses 1 and 2 of a three dose schedule. Results Vaccine uptake was 70.6% (1989/2817) for the first dose and 68.5% (1930/2817) for the second dose. Uptake was significantly lower in schools with a higher proportion of ethnic minority girls (P<0.001 for trend) or higher proportion of girls entitled to free school meals (P=0.029 for trend). The main reason for parents' refusal of vaccination was insufficient information about the vaccine and its long term safety. Maintaining the vaccine schedule was challenging as 16.3% (dose 1) and 23.6% (dose 2) of girls missed their vaccination day and had to be offered alternative appointments. No serious adverse events were reported. Conclusion Delivery of the first two doses of HPV vaccine to adolescent schoolgirls is encouraging, but the success of the vaccination programme depends on high coverage for the third dose.